2022
DOI: 10.1001/jamanetworkopen.2022.2735
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Losartan in Hospitalized Patients With COVID-19–Induced Lung Injury

Abstract: IMPORTANCE SARS-CoV-2 viral entry may disrupt angiotensin II (AII) homeostasis, contributing to COVID-19 induced lung injury. AII type 1 receptor blockade mitigates lung injury in preclinical models, although data in humans with COVID-19 remain mixed. OBJECTIVE To test the efficacy of losartan to reduce lung injury in hospitalized patients with COVID-19. DESIGN, SETTING, AND PARTICIPANTS This blinded, placebo-controlled randomized clinical trial was conducted in 13 hospitals in the United States from April 202… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 48 publications
1
42
0
1
Order By: Relevance
“…The findings from CLARITY are largely consistent with five previous trials in which 593 participants previously untreated with a renin angiotensin system inhibitor were randomly assigned to receive treatment with an ARB. 21 22 23 24 25 Four trials, which randomly assigned 435 participants, reported no effect on the primary outcomes of 30 day mortality, 23 length of hospital stay, 23 a composite of mechanical ventilation or death, 22 lung injury, 24 and all cause hospital admission (among patients not admitted to hospital). 25 Additionally, no effect was reported for most of the secondary outcomes examined.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from CLARITY are largely consistent with five previous trials in which 593 participants previously untreated with a renin angiotensin system inhibitor were randomly assigned to receive treatment with an ARB. 21 22 23 24 25 Four trials, which randomly assigned 435 participants, reported no effect on the primary outcomes of 30 day mortality, 23 length of hospital stay, 23 a composite of mechanical ventilation or death, 22 lung injury, 24 and all cause hospital admission (among patients not admitted to hospital). 25 Additionally, no effect was reported for most of the secondary outcomes examined.…”
Section: Discussionmentioning
confidence: 99%
“…How beneficial are ACE2-modulating medications, such as ACE inhibitors or ang II receptor blockers (ARBs)? Recent clinical study ( 173 ) suggested that oral administration of 50-mg losartan, an ARB, for 10 days did not improve arterial partial pressure of oxygen to fraction of inspired oxygen ( : ) ratio in the hospitalized patients with COVID-19 and acute lung injury. Further studies are needed with large cohort studies under acute as well as chronic conditions to understand further details.…”
Section: Future Perspectives and Unanswered Questionsmentioning
confidence: 99%
“…However, in a blinded, placebo-controlled randomized clinical trial Lor did not improve the health state of hospitalized COVID-19 patients. A maximal Lor dose did not reduce lung injury, which was measured with the oxygenation ratio (PaO 2 :FiO 2 ) [ 62 ]. It is worth mentioning that there is also a promising study regarding the use of AT1R blockers to inhibit NLRP3 inflammasomes [ 63 ].…”
Section: At1r Antagonistsmentioning
confidence: 99%